The Concept and Criteria of Insignificance of the Committed Administrative Offense - A. V. Popov; I. A. Fomina (Сибирское юридическое обозрение, 2023)
The problem of applying the insignificance of administrative offenses is relevant in the scientific community. Many authors, such as Yu. P. Solovey, E. V. Sergeeva, O. V. Derbina, L. Ch. Kupeeva and others, in different years raised issues related to the insignificance of offenses in their scientific activities. The Authors studied the objectivity of the application of insignificance to the formal elements of offenses, the effectiveness of oral remarks, and possible criteria for recognizing an offense as insignificant. The appraisal of the concepts enshrined in the Code of Administrative Offenses of the Russian Federation (hereinafter referred to as the Code of Administrative Offenses of the Russian Federation) makes it possible to ensure the flexibility of legislation in sentencing. However, in the particular case under consideration, evaluativeness and the lack of clear criteria for the use of insignificance contribute to the blurring of the boundaries of responsibility. The results of the statistical study cited by the Authors show that for 2019–2021. a significant number of proceedings on administrative offenses were terminated precisely on the basis of Art. 2.9 of the Code of the Russian Federation on Administrative Offenses, which indicates the importance of the criteria by which the possibility of applying insignificance and the conditions to be analyzed by an official of the relevant administrative body or a judge is assessed. As a criterion of insignificance of administrative offenses, the objective side of which is characterized by the receipt of income or damage, the Authors propose to use the amount of such income or damage. According to the Authors, the classification of an administrative tort as insignificant is possible when receiving income or causing damage that does not exceed 1/30 of the subsistence minimum in the whole of the Russian Federation per capita, provided for the calendar year in which the administrative offense was committed (for 2023 – 480 rubles). Given the above, the Authors indicate the need for legislative consolidation of the categories of administrative offenses and circumstances in the commission or occurrence of which the application of the legal institution of insignificance is unacceptable. One of these circumstances, at the suggestion of the Authors, is the absence of a person held liable when considering a case of an administrative offense.